1989
DOI: 10.1111/j.1365-2133.1989.tb01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi-like acroangiodermatitis in an above-knee amputation stump

Abstract: The clinical, histological and immunohistological features of a Kaposi-like acroangiodermatitis in an above-knee amputation stump are reported. There was no evidence for an underlying arteriovenous malformation and the irregular purple-blue skin lesions resulted from chronic circulatory disturbance of the distal stump caused by a poorly fitting suction-type prosthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…Ulcers [10][11], epidermoid cysts [8,10], Kaposi-like sarcoma [12][13], and verrucous hyperplasia [10,[14][15] are skin conditions that are attributed to external pressures applied to the residual limb. Sustaining proper circulation and fluid exchange in the soft tissues is imperative for maintaining a healthy residual limb.…”
Section: Introductionmentioning
confidence: 99%
“…Ulcers [10][11], epidermoid cysts [8,10], Kaposi-like sarcoma [12][13], and verrucous hyperplasia [10,[14][15] are skin conditions that are attributed to external pressures applied to the residual limb. Sustaining proper circulation and fluid exchange in the soft tissues is imperative for maintaining a healthy residual limb.…”
Section: Introductionmentioning
confidence: 99%
“…17 Pseudo-Kaposi sarcoma has also been reported as being associated with trauma. [17][18][19][20] Recently, Trindade et al reported a case of pseudoKaposi sarcoma due to suction-socket lower limb prosthesis 7 that shares some of the features found in our biopsy, but their lesion did not show the promontory sign. Trindade et al specifically insisted that ''in contrast with patch stage lesions of Kaposi's sarcoma, proliferation of irregular jagged vascular channels, with slit-like lumina, surrounding pre-existing capillaries is not seen in lesions of pseudo-Kaposi's sarcoma.''…”
Section: Discussionmentioning
confidence: 71%
“…16 Repeated microtrauma to the skin of the stump may occur if the fit of socket and stump is not perfect, leading to proliferation of fibroblasts and small vessels and in particularly sensitive tissue such as the skin on an amputation stump. 17 Acroangiodermatitis occurring on amputation stumps because of socket prostheses is clinically reported as a stump edema with violaceous macules, patches and nodules. 2,16,17 There is one report of amputation stump dermatitis, clinically resembling verrucous hyperplasia, but with predominant histologic aspects of acroangiodermatitis in a patient with a suction-socket lower limb prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…17 Acroangiodermatitis occurring on amputation stumps because of socket prostheses is clinically reported as a stump edema with violaceous macules, patches and nodules. 2,16,17 There is one report of amputation stump dermatitis, clinically resembling verrucous hyperplasia, but with predominant histologic aspects of acroangiodermatitis in a patient with a suction-socket lower limb prosthesis. 11 Histopathologic findings of early lesions are those of an exaggerated stasis dermatitis, including increased number of thick-walled capillaries and venules lined by plump endothelial cells, extravasation of erythrocytes and deposits of hemosiderin.…”
Section: Discussionmentioning
confidence: 99%